Respuesta :
1.
x - 1 = 5
x = 5 - 1
x = 4
2.
2(x-1)=10
2x - 2 = 10
2x = 10 + 2
2x = 12
x = 12÷2
x = 12/2
x = 6
3.
3(x-1)=15
3x - 3 = 15
3x = 15 + 3
3x = 18
x = 18÷3
x = 18/3
x = 6
Answer:
1) x = 6
2) x = 6
3) x = 6
Step-by-step explanation:
Concept :
Here, we will use the below following steps to find a solution using the transposition method:
- Step 1 :- we will Identify the variables and constants in the given simple equation.
- Step 2 :- then we Simplify the equation in LHS and RHS.
- Step 3 :- Transpose or shift the term on the other side to solve the equation further simplest.
- Step 4 :- Simplify the equation using arithmetic operation as required that is mentioned in rule 1 or rule 2 of linear equations.
- Step 5 :- Then the result will be the solution for the given linear equation.
Solution :
1) x-1=5
[tex]\begin{gathered} \qquad{\longrightarrow{\tt{x - 1 = 5}}} \\ \\ \qquad{\longrightarrow{\tt{x = 5 + 1}}} \\ \\ \qquad{\longrightarrow{\tt{\underline{\underline{\red{x = 6}}}}}}\end{gathered}[/tex]
- Hence, the value of x is 6.
[tex]\begin{gathered}\end{gathered}[/tex]
2) 2(x-1)=10
[tex]\begin{gathered} \qquad{\dashrightarrow{\tt{2(x - 1) = 10}}} \\ \\ \qquad{\dashrightarrow{\tt{2 \times x - 2 \times 1 = 10}}} \\ \\ \qquad{\dashrightarrow{\tt{2x - 2 = 10}}} \\ \\ \qquad{\dashrightarrow{\tt{2x = 10 + 2}}} \\ \\ \qquad{\dashrightarrow{\tt{2x = 12}}} \\ \\ \qquad{\dashrightarrow{\tt{x = \dfrac{12}{2}}}} \\ \\ \qquad{\dashrightarrow{\tt{\underline{\underline{\pink{x = 6}}}}}}\end{gathered}[/tex]
- Hence, the value of x is 6.
[tex]\begin{gathered}\end{gathered}[/tex]
3) 3(x-1)=15
[tex]\begin{gathered} \qquad{\longmapsto{\tt{3(x - 1) = 15}}}\\\\\qquad{\longmapsto{\tt{3 \times x - 3 \times 1 = 15}}}\\\\\qquad{\longmapsto{\tt{3x - 3 = 15}}}\\\\\qquad{\longmapsto{\tt{3x = 15 + 3}}}\\\\\qquad{\longmapsto{\tt{3x = 18}}}\\\\\qquad{\longmapsto{\tt{x = \dfrac{18}{3}}}}\\\\\qquad{\longmapsto{\tt{\underline{\underline{\purple{x = 6}}}}}}\end{gathered}[/tex]
- Hence, the value of x is 6.
[tex]\rule{300}{2.5}[/tex]